2022
DOI: 10.1167/jov.22.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Grasping follows Weber's law: How to use response variability as a proxy for JND

Abstract: Weber's law is a fundamental psychophysical principle. It states that the just noticeable difference (JND) between stimuli increases with stimulus magnitude; consequently, larger stimuli should be estimated with larger variability. However, visually guided grasping seems to violate this expectation: When repeatedly grasping large objects, the variability is similar to that when grasping small objects. Based on this result, it was often concluded that grasping violated Weber's law. This astonishing finding gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Here we found that actions obey Weber's law. The SD of the final inter-finger separation increased as a function of the inter-target distance, with a slope ranging from 0.012 to 0.038, in line with the classic and modern literature on Weber's law (e.g., Bhatia et al, 2022;Derzsi & Volcic, 2023;Fechner, 1860;Hesse et al, 2021;McKee & Welch, 1992;Teghtsoonian, 1971).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here we found that actions obey Weber's law. The SD of the final inter-finger separation increased as a function of the inter-target distance, with a slope ranging from 0.012 to 0.038, in line with the classic and modern literature on Weber's law (e.g., Bhatia et al, 2022;Derzsi & Volcic, 2023;Fechner, 1860;Hesse et al, 2021;McKee & Welch, 1992;Teghtsoonian, 1971).…”
Section: Discussionsupporting
confidence: 83%
“…However, it should be noted that recent studies have suggested that SD MGA may not accurately reflect the precision with which visual size is discriminated. In particular, Bhatia et al (2022) demonstrated that using MGA as a proxy for the corresponding final estimation response can erroneously mask Weber's law because the response function of MGA is non-linear. When this non-linear scaling is appropriately considered, Weber's law can be detected even in grasping movements.…”
Section: Discussionmentioning
confidence: 99%